Pengembangan Media Stopmotion Berbantuan Storytelling Pada Pembelajaran IPS SD - Yansaputra, Galih; Pangestika, Rintis Rizkia (Universitas Muhammadiyah Magelang, 2020)
Social studies learning problem is an urgent problem and it is necessary to immediately find alternative solutions to problems to improve and improving the quality of social studies learning at SDN 2 Pangenjurutengah. Research that has the aim of increasing the motivation for learning Social Sciences at SD Negeri 2 Pangenjurutengah is increasing. To overcome these learning problems, it is necessary to apply innovative learning models that can increase student motivation including teacher skills, student activities, and student learning outcomes that encourage active student involvement in learning. The subjects studied in this study were SD Negeri 2 Pangenjurutengah, Class IV 2018/2019 Academic Year. The type of methods use in this research is development or Research and Development (R&D). The resulting product is social studies learning with stopmotion media assisted by storytelling consisting of learning media, teacher's books and students. The instrument used was tested for validity and reliability testing. Before analyzing the data, the analysis prerequisite test was carried out which consisted of a normality test. The results of the study obtained a validation score of 77.6% of material experts and a score of 78.9% of media experts. Data collection using a questionnaire in the learning model, usability, media design, material coverage of Elementary School Social Sciences obtained by the prerequisite analysis test, namely the normality test getting a score of 0.546> 0.05 (Kolmogorov Smirnov table) so that the distribution is normal. Hypothesis testing or t test get sig.0.000 <0.05 and t count 0.76 <1.69 (t table). From the results of the research conducted, it can be concluded that the stopmotion media is to increase the motivation of elementary school students in social studies learning.